Promotion, Brand Image, and Customer Relationship Management on Aluminum Purchase Decisions at PT Global Alumindo Perkasa - Purba, Jansaris Othniel; Christina, Cindy; Wijaya, Evelyn; Andi; Syahputra, Hidayat (Luxury: Landscape of Business Administration, 2023)
The purpose of this study was to determine and analyze the effect of promotion, brand image, and customer relationship management on purchasing decisions. This research was conducted at PT Global Alumindo Perkasa which is located at Jalan Soekarno-Hatta No.9 Pekanbaru. The population of this study is consumers who make purchases at PT Global Alumindo Perkasa, so the sample in this study is 120 with an accidental sampling technique. Data analysis using multiple linear regression. The results of the study explain that promotion and customer relationship management have a positive and significant influence, while the brand image has a positive and insignificant effect on purchasing decisions. For further researchers, it is expected to develop this research by adding other variables.